2018
DOI: 10.1111/are.13737
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on zinc bioavailability of different sources and dietary zinc requirement in juvenile grouperEpinephelus coioides

Abstract: An experiment was implemented to study the effect of dietary zinc levels from three zinc sources on growth performance, immunity, and tissue mineral elements deposition on juvenile grouper. Based on the zinc free feeds, dietary zinc levels of 0, 10, 20, 40, 80, and 160 mg/kg were added from zinc sulphate (ZnSO 4 ), tetrabasic zinc chloride (TBZC), and 2-hydroxy-4-(methylthio) butyrate zinc (Zn-HMB). The results of the 8-week study indicated that the weight gain rate (WGR) and specific growth rate (SGR) at leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 57 publications
1
17
0
Order By: Relevance
“…Muthuraman and co‐workers were postulated that the antioxidative effect of Zn may be related to mRNA expression of antioxidant enzyme (Muthuraman et al, 2014). Moreover, Huang and co‐workers found that increasing the organic Zn (2‐hydroxy‐4‐(methylthio) butyrate Zn) level in diet can significantly increase live catalase (CAT), T‐SOD and Cu‐Zn SOD activity of fish (Huang et al, 2018). Also, MDA content in sauvage ( Paramisgurnus dabryanus ) was obviously decreased with the increase of dietary Zn Methionine levels (Du et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Muthuraman and co‐workers were postulated that the antioxidative effect of Zn may be related to mRNA expression of antioxidant enzyme (Muthuraman et al, 2014). Moreover, Huang and co‐workers found that increasing the organic Zn (2‐hydroxy‐4‐(methylthio) butyrate Zn) level in diet can significantly increase live catalase (CAT), T‐SOD and Cu‐Zn SOD activity of fish (Huang et al, 2018). Also, MDA content in sauvage ( Paramisgurnus dabryanus ) was obviously decreased with the increase of dietary Zn Methionine levels (Du et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Noteworthy, Zn not only as a cofactor for cytoplasm and extracellular SOD, but also plays an important role in gene regulation in lymphocytes (Sallam et al, 2020). Some studies started that Zn supplementation augmented the non‐specific innate immunological response (e.g., lysozyme activities) in Nile tilapia (Awad et al, 2019; Huang et al, 2018). Recent study also demonstrated that Nile tilapia fed with organic Zn (Zn Methionine) displayed significantly higher immune responses and resistance to bacterial infection than inorganic Zn treatment (Kishawy et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, our results suggested that NCM-Cu as a Cu additive alleviated the oxidative stress and lipid peroxidation. 48 …”
Section: Resultsmentioning
confidence: 99%
“…Biological availability of Fe measured by a hemoglobin regeneration assay in Atlantic salmon showed that the relative availability of Fe from ferric chloride, ferric oxide, blood meal and herring meal was 98.8, 17.8, 52.3 and 47.1%, respectively (Naser, 2000). However, higher bioavailability of iron from blood meal (Andersen et al, 1997), Fe-hydroxy methionine analogue (Huang et al, 2018) and Fe-methionine (Qiao et al, 2013) have been reported for Atlantic salmon, grouper and cobia respectively. The quality of blood meal varies widely in terms of protein quality.…”
Section: Bioavailabilitymentioning
confidence: 99%